Stylistic Compensation into Lesia Ukrainka’s Russian Translations of Ivan Franko’s Stories (Linguostylistic Studies, 2014)
The article is devoted to the detailed lexis comparative analyze of the original and translation (the material of the investigation is 6 stories by Ivan Franko and its remarkable Russian version translated by Lesia Ukrainka). The main aim of this research is to elucidate possible means of  the semantic and stylistic losses  into the artistic translations of close related Slavic languages (Ukrainian-Russian). The overcoming of language barrier in the translation mainly lies in the creative encoding of the words with expressive ethno cultural coloring. Therefore, the original components, that have no equivalents in any translation, are a justifiable and natural phenomenon. In the translations of close related Slavic languages the possibilities of encoding such units are much bigger than in case with unrelated languages. The following formations, which cannot be translated, have been researched: words-realities (historical, everyday), dialecticisms, colloquialisms, definite word forms. It is shown, that the major ways of reproduction of specific Ukrainian components in this Russian translation are transcription and transliteration, and constructions after foreign patterns (analogy), and also using lexical units from the sphere of limited or colloquial use. Key words: theory of translation, Slavonic languages, artistic translation, an unequivalent lexis, stylistic compensation. References